Recyclable Time–Temperature Indicator Enabled by Light Storage in Particles. Issue 8 (17th February 2023) - Song, Yifan; Du, Jiaren; Yang, Rujun; Lin, Cunjian; Chen, Wenjing; Wu, Zishuang; Lin, Hengwei; Chen, Xi; Zhuang, Yixi; Xie, Rong‐Jun
Abstract: Time–temperature indicator (TTI) technologies allow for nondestructive and real‐time quality management of perishable products during the entire transport–storage process, which provides an important guarantee for the product safety of end users. However, the existing TTI technologies still have shortcomings in recyclability, sensitivity, and environmental tolerance, limiting their widespread applications. Herein, a new TTI route based on the light storage effect in persistent luminescent (PersL) materials is proposed. Such TTI is designed on account of the principle that the release rate of light‐induced trapped carriers in PersL materials is closely dependent on the storage time and temperature, enabling to establish a correlation between the number of residual carriers and the freshness of perishable products. Taking KZnF3 :Mn 2+ as a model material, the light‐storage‐based TTI technology shows excellent recyclability, reliability, and environmental stability. This work reveals great potentials of PersL phosphors as information recording materials in advanced TTI application and next‐generation biological detection technology. Abstract : A time–temperature indicator method based on the light‐storage effect in persistent luminescence materials is proposed for the first time. Such time–temperature indicators show excellent recyclability, reliability, and environmental stability, and exhibit great prospects in next‐generation intelligent packaging technology and biological detection technology.